Youth gangs in a remote Indigenous community: importance of cultural authority and family support - Teresa Cunningham
Wadeye is one of the largest Indigenous communities in the Northern Territory. Over the past decade, the community has attracted much negative media attention because of the amount of violence that has occurred. This violence has often been portrayed as the result of gang activity. This paper examines how gangs operate in the Wadeye community and provides some insight into the perceptions of gang members on their relationships with community authority structures and family support mechanisms. The researchers found that the criminal aspects of gang membership may be less important than factors such as identity construction, experiments with leadership and preservation of knowledge about culture and history. Authored by Teresa Cunningham, Bill Ivory, Richard Chenhall, Rachael McMahon and Kate Senior